Is the great decoupling real? - Škare, Marinko; Škare, Damian (Journal of Business Economics and Management, 2017)
The great decoupling is real. Productivity and employment/wages link changed after 1980 in many countries, not just the U.S. This study investigates the productivity and employment/wages link (1950–2014) looking for empirical proof of the “great decoupling” put forward by Brynjolfsson and Mcafee (2013). The results should stimulate policymakers to openly question why real wages and productivity don’t line up with the theory. We use the Hodrick and Prescott (1997) filter to isolate trends in real wages, labor share in GDP, and labor productivity and rolling correlation to explore if the great decoupling is real. We have found that the great decoupling i.e. The divergence between real wages/employment and productivity is present in all countries (10 in the sample). The dynamics of the great decoupling are however different between the countries although year 1980 seems to be a dominant breaking point for the start of the phenomena. This paper provides multicounty empirical proof of the presence of the great decoupling phenomena and explores its dynamics over 1950–2014. Policy makers as well as firms and unions should take the existence of this phenomena seriously since it can have significant consequences on economic growth and labor markets’ functioning.